Probing into Thailand's basement: New insights from U–Pb geochronology, Sr, Sm–Nd, Pb and Lu–Hf isotopic systems from granitoids - Dew, R.; Collins, A.; Glorie, S.; Morley, C.; Blades, M.; Nachtergaele, S.; King, R.; Foden, J.; De Grave, J.; Kanjanapayont, P.; Evans, Noreen; Alessio, B.; et al. (Elsevier BV, 2018)
• εHf–Nd(t) model is increasingly juvenile eastwards in Thailand.